Mathematics methods problems in periodical in Lithuania between the two world wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2009)
The mathematics methods problems in periodical between the two world wars are introduced in article. The education fractions are analyzed. Problems in education solve equations, rate problems and arithmetic are described.